2014
DOI: 10.1111/1911-3838.12023
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Psychometric Properties of the Perceived Stress Scale-10 (PSS10) with Business and Accounting Students

Abstract: Using a sample of 557 undergraduate business students from three U.S. comprehensive universities, this study examined: (a) the factor structure of the Perceived Stress Scale‐10 (PSS10; Cohen and Williamson, 1988); (b) the invariance of its factor structure; (c) the scale's reliability; and (d) its convergent and divergent validity. Confirmatory factor analyses supported a structure with two primary factors, General Distress and Ability‐to‐Cope, loading on a single second‐order factor, Perceived Stress. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 43 publications
4
36
0
4
Order By: Relevance
“…Several authors have found gender differences in perceived stress in different student samples, all reporting females to have a higher level of perceived stress when compared to males (Andreou et al 2011;Leung et al 2010;Örücü and Demir 2009;Remor et al 2006;Roberti et al 2006;Smith et al 2014). Data from the current study supports this notion, concluding that female students were significantly more susceptible to stress compared to males (19.16 vs. 15.52 respectively).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Several authors have found gender differences in perceived stress in different student samples, all reporting females to have a higher level of perceived stress when compared to males (Andreou et al 2011;Leung et al 2010;Örücü and Demir 2009;Remor et al 2006;Roberti et al 2006;Smith et al 2014). Data from the current study supports this notion, concluding that female students were significantly more susceptible to stress compared to males (19.16 vs. 15.52 respectively).…”
Section: Discussionsupporting
confidence: 76%
“…As it is difficult to generalise a normative perceived stress score due to a number of confounding variables, it may be more appropriate to compare our findings to a student only population. In this context the average score reported in this paper is comparable to scores of ~17 (Roberti et al 2006) and ~16 (Smith et al 2014) from the USA, and ~19 from Turkey (Örücü and Demir 2009).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations